CEDAR a core-extraction distributed ad hoc routing algorithm. - Sivakumar, R. (IEEE Journal on selected areas in communications)
We present CEDAR, a core-extraction distributed ad hoc routing algorithm for quality-of-service (QoS) routing in ad hoc network environments, CEDAR has three key components: (a) the establishment and maintenance of a self-organizing routing infrastructure called the core for performing route computations; (b) the propagation of the link-state of high bandwidth and stable links in the core through increase/decrease waves; and (c) a QoS-route computation algorithm that is executed at the core nodes using only locally available state. The performance evaluations show that CEDAR is a robust and adaptive QoS routing algorithm that reacts quickly and effectively to the dynamics of the network while still approximating the performance of link-state routing for stable networks